2011
DOI: 10.1007/s11726-011-0549-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moxibustion therapy on preventing and treating side effects from chemotherapy of malignant tumor patients

Abstract: 【摘要】目的:观察灸法治疗恶性肿瘤患者化疗毒副反应的临床疗效。方法:将 63 例恶性肿瘤患者随机 分为 3 组。艾灸组 23 例,采用灸法治疗;水针组 22 例,采用穴位注射治疗;对照组 18 例,采用口服鲨 肝醇治疗。观察各组患者治疗前后白细胞总数及免疫球蛋白含量的变化。结果:治疗后艾灸组、水针组 白细胞总数及免疫球蛋白含量均有提高, 与对照组有统计学差异(P<0.05, P<0.01);在提高白细胞总数方面, 水针组优于艾灸组(P<0.05)。结论:艾灸、水针可防治恶性肿瘤化疗毒副反应;在防治恶性肿瘤化疗毒副 反应方面,不同针灸方法具有不同的效果。 【关键词】灸法;悬灸;水针;药物疗法;药物毒性;抗肿瘤联合化疗方案;肿瘤 【中图分类号】R246.5 【文献标识码】A 【Abstract】 Objective:To observe the clinical effects of moxibustion therapy on preventing and treating toxic and side effects of chemotherapy in malignant tumor patients. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…These results are consistent with a previous study which found that moxibustion could improve the total number of leukocytes in 23 patients with malignant tumors of the respiratory and digestive systems after chemotherapy. 13 In this study, we found that moxibustion could improve the antitumor effect of paclitaxel by reducing the total number of WBCs. The growth and metastasis of a tumor depend on the formation of neovascularization.…”
Section: Discussionmentioning
confidence: 71%
“…These results are consistent with a previous study which found that moxibustion could improve the total number of leukocytes in 23 patients with malignant tumors of the respiratory and digestive systems after chemotherapy. 13 In this study, we found that moxibustion could improve the antitumor effect of paclitaxel by reducing the total number of WBCs. The growth and metastasis of a tumor depend on the formation of neovascularization.…”
Section: Discussionmentioning
confidence: 71%